Gramapanchayats and Continuing Education Centres in Karnataka : Where Rubber Hits the Road - Nanjunda (KILA Journal of Local Governance, 2013)
The strong grass root democracy is one of the founding stones for success or failure of any literacy programme. The fundamental aim behind Continuing Education Centre (CEC) is to provide opportunity for the neo-learners to learn new things to upgrade their literacy skills acquired under Total Literacy and Post Literacy Programmes. Basically one CEC will be setup to cater to the need of population of 500-2000 with a voluntary teacher (Prerakas). Grama Panchyaths (GPs) are assigned to manage CECs in each village. For every 10-12 CECs, a nodal centre has been established. This is a summary of paper findings of a study conducted in selected districts of Karnataka and bring to light the experience of GPs in administering Continuing Education Centres (CECs).